Operation control and generation optimization of standalone distributed energy resources - Sun, Zhicheng. (2011)
With the increasing development and penetration of microgrids using distributed resources such as wind energy and solar energy to address environmental and energy policy concerns, the generation optimization and operation control of microgrid have become more and more important. In this project, the microgrid operates in standalone mode, which means that they are not connected with any other power grids. Operating the power system so that the cost could be minimized becomes the main concern. In order to achieve that, firstly, the unit commitment problem and a MILP model is introduced. The model includes the operating cost, spinning reserve cost and constraints such as unit generating constraints, generation and spinning reserve constraints, unit operating constraints and unit start-up constraints. Two case studies consist of a power system of 26 units are conducted. The solution is justified by comparing it with Dr. Liang Hongzhu's solution, the Laboratory for Clean Energy Research. Secondly, the proposed model is modified accordingly to integrate well with the existing MG-EMS. A LabVIEW graphic user interface (GUI) is developed for displaying the forecasted load and the operating schedule.